Malaysian muslim consumer credit card usage behavior - Farid, Muhammad (2015)
The objective of this study aims to identify Malaysian Muslim consumer credit card usage behaviour. This study also identifies financial knowledge, attitude toward credit card, bank policies and lifestyle toward Malaysian Muslim consumer credit card usage behaviour. There were 86 people being chosen to be the respondent of this study by the simple random sampling method. The results which were being tested by multiple regression showed that there were significant relationship between financial knowledge and bank policies which Malaysian Muslim consumer credit card usage behaviour, financial knowledge (β=0.171, p<0.05), bank policies (β=0.677, p<0.05) while there were no significant relationship between attitude toward credit card and lifestyle with Malaysian Muslim consumer credit card usage behaviour (β=0.086, p>0.05) (β= 0.066, p>0.05). In addition, the findings which were being tested using Pearson correlation showed that there was a significant relationship between financial knowledge and bank policies with Malaysian Muslim consumer credit card usage behaviour (r 0.047, p<0.05) (r 0.000, p<0.05) and also there was no significant relationship between attitude toward credit card and lifestyle with Malaysian Muslim consumer credit card usage behaviour(r 0.387, p>0.05) (r 0.424, p>0.05). Therefore, this study concludes that financial knowledge and bank policies influencing the Malaysian consumer credit card usage behaviour. Meanwhile, attitude toward credit card and lifestyle not influencing Malaysian Muslim consumer credit card usage behaviour. To get better and accurate results, future research should increase sample size to a bigger geographic areas and larger sample and it is recommended to determine other factors which might affect Malaysian Muslim consumer credit card usage behaviour. Future research should focus on developing a consistent measure of attitude toward credit or Muslim lifestyle and also examine the relationship between Islamic financial knowledge and a variety of personal attitudes other than credit card usage behaviour